Fast-charging negative electrode material and preparation method and application thereof

By introducing nitrogen and phosphorus co-doping functionalized carbon nanotubes into the hard carbon anode material of sodium ion batteries, using microwave processing technology, the problems of low conductivity and poor structural stability of hard carbon materials are solved, and efficient fast charging and Long cycle life.

CN119447289APending Publication Date: 2025-02-14CARBON ONE NEW ENERGY GRP CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361097.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The negative electrode materials of existing sodium ion batteries, especially hard carbon materials, have low conductivity, resulting in poor kinetic performance and difficult to meet the needs of fast charging. At the same time, strategies such as structural design and chemical modification will affect their structural stability and cycle life. .

Method used

A hard carbon material co-doped with nitrogen and phosphorus is used, and functionalized carbon nanotubes are grown on its surface. Through the synergistic action of microwave processing technology, electronic structure and structural stability are optimized and the wetting and kinetic properties of the electrolyte are improved.

Benefits of technology

The fast-charging negative electrode material has achieved a combination of conductivity, specific capacity and structural stability, meeting the needs of high-rate fast-charging batteries, and is especially suitable for sodium ion fast-charging batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447289A_ABST
    Figure CN119447289A_ABST
Patent Text Reader

Abstract

The invention relates to a fast-charging negative electrode material as well as a preparation method and application thereof. The fast charge negative electrode material comprises nitrogen and phosphorus co-doped hard carbon and functionalized carbon nanotubes distributed on the surface of the nitrogen and phosphorus co-doped hard carbon; in the fast-charging negative electrode material, the content of a nitrogen element is 0.70 wt%-6.00 wt%, the content of a phosphorus element is 1.45 wt%-3.00 wt%, and the content of functional groups on the surface of the fast-charging negative electrode material comprises at least one of the following items (1)-(4): (1) 0.05 wt%-0.1 wt% of carboxyl based on oxygen atoms; (2) 0.05 wt% to 0.2 wt% of a carbonyl group; (3) 0.2 wt% to 0.4 wt% of an alkoxy group; and (4) 0.1 wt% to 0.2 wt% of hydroxyl groups. The fast-charging negative electrode material disclosed by the invention has conductivity, specific capacity and structural stability at the same time, and can meet the requirements of high-rate fast-charging batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a fast-charging negative electrode material and a preparation method and application thereof. Background Art

[0002] As the global demand for clean energy grows, sodium-ion batteries, as a new type of secondary battery, have attracted widespread attention due to their advantages such as abundant resources, low cost and high safety. However, the performance of sodium-ion batteries, especially the performance of their negative electrode materials, is still a key factor restricting their development.

[0003] Among them, hard carbon is a negative electrode material with high specific capacity and long cycle life, but its low electrical conductivity leads to poor kinetic performance and makes it difficult to meet the needs of fast charging. From a material perspective, although the kinetic properties of hard carbon negative electrodes can be improved through strategies such as structural design, chemical modification, and surface coating, and the fast charging performance of hard carbon negative electrodes can be improved, it will also cause problems such as poor structural stability and reduced specific capacity, thereby affecting its cycle life. Therefore, it is urgent to provide a hard carbon negative electrode material that takes into account conductivity, specific capacity, and structural stability. Summary of the invention

[0004] Based on this, it is necessary to provide a fast-charging negative electrode material and its preparation method and application to address the above problems; the fast-charging negative electrode material takes into account conductivity, specific capacity and structural stability at the same time, and can meet the needs of high-rate fast-charging batteries.

[0005] A fast-charging negative electrode material, comprising nitrogen-phosphorus co-doped hard carbon and functionalized carbon nanotubes distributed on the surface of the nitrogen-phosphorus co-doped hard carbon;

[0006] In the fast-charging negative electrode material, the content of nitrogen is 0.70wt%-6.00wt%, the content of phosphorus is 1.45wt%-3.00wt%, and the functional group content on the surface of the fast-charging negative electrode material includes at least one of the following (1)-(4): in terms of oxygen atoms,

[0007] (1) 0.05wt%-0.1wt% of carboxyl groups;

[0008] (2) 0.05wt%-0.2wt% carbonyl;

[0009] (3) 0.2 wt% to 0.4 wt% of alkoxy;

[0010] (4) 0.1 wt% to 0.2 wt% of hydroxyl groups.

[0011] In one embodiment, the fast-charging negative electrode material satisfies at least one of the following conditions:

[0012] (1) The (002) crystal plane spacing of the fast-charging negative electrode material is 0.38 nm-0.39 nm;

[0013] (2) The mass of the functionalized carbon nanotubes is 0.1%-2% of the mass of the nitrogen-phosphorus co-doped hard carbon;

[0014] (3) The specific surface area of ​​the fast-charging negative electrode material is 5.5 m 2 / g-6.5m 2 / g;

[0015] (4) The pore volume of the fast-charging negative electrode material is 0.0175 cm 3 / g-0.0250cm 3 / g;

[0016] (5) D of the fast-charging negative electrode material 50 5.2μm-6.5μm;

[0017] (6) K of the fast-charging negative electrode material 90 is 1.20-1.55, among which, K 90 =(D 90 -D 10 ) / D 50 .

[0018] In the fast-charging negative electrode material described in the present invention, under the synergistic effect of specific contents of nitrogen and phosphorus elements and surface functionalized carbon nanotubes, not only can the electronic structure of the fast-charging negative electrode material be optimized, while the interlayer spacing is expanded, its structural stability is ensured, so that the fast-charging negative electrode material can take into account both conductivity and structural stability, but it is also beneficial to improve the wettability of the electrolyte to the fast-charging negative electrode material, promote material exchange on the negative electrode interface, enhance the kinetic performance of the fast-charging negative electrode material, and ensure the specific capacity while improving the conductivity.

[0019] A method for preparing the fast-charging negative electrode material as described above comprises the following steps:

[0020] The pretreated biomass carbon source is reacted with a solution containing a nitrogen source and a phosphorus source to obtain a precursor, and the precursor is subjected to carbonization treatment to obtain nitrogen-phosphorus co-doped hard carbon;

[0021] After the nitrogen-phosphorus co-doped hard carbon is mixed with an iron-containing organic compound solution for impregnation reaction, carbon nanotubes are grown in situ on the surface of the nitrogen-phosphorus co-doped hard carbon through a first microwave reaction to obtain a pre-product, wherein the power of the first microwave reaction is P1 and the time is t1;

[0022] The pre-product is subjected to a second microwave reaction to obtain the fast-charging negative electrode material, wherein the power of the second microwave reaction is P2 and the time is t2.

[0023] In one embodiment, 500W≤P1≤1500W, 20s≤t1≤100s;

[0024] and / or, 200W≤P2≤600W, 1s≤t2≤10s;

[0025] And / or, (P1-P2) / P1≥0.5, (t1-t2) / t2≥5.

[0026] In one embodiment, the first microwave reaction and the second microwave reaction further satisfy at least one of the following conditions:

[0027] (1) The microwave frequencies of the first microwave reaction and the second microwave reaction are each independently selected from 2 GHz to 3 GHz;

[0028] (2) the second microwave reaction is carried out in a mixed gas environment of H2 and CO2, wherein the volume ratio of H2 to CO2 is 1:5-2:1;

[0029] (3) The pressure of the second microwave reaction is 15Pa-30Pa.

[0030] In one embodiment, the impregnation reaction step satisfies at least one of the following conditions:

[0031] (1) The mass ratio of the nitrogen and phosphorus co-doped hard carbon to the iron-containing organic compound solution is 1:10-1:1;

[0032] (2) the iron-containing organic compound comprises at least one of heme, heme, ferrous ferrocyanide, ferrous ethylenediaminetetraacetate, and ferrocene;

[0033] (3) In the iron-containing organic compound solution, the solvent is selected from a mixed solvent of ethanol and water, wherein the volume ratio of ethanol to water is 1:2-2:1;

[0034] (4) The impregnation reaction time is 0.5h-2h, and the stirring rate is 120rpm-300rpm.

[0035] In one embodiment, the pretreatment includes: stirring the biomass carbon source and the treatment solvent at 60°C-100°C at a speed of 50rpm-200rpm for 2h-8h, and then washing the reacted biomass carbon source to a neutral pH and drying it.

[0036] In one embodiment, the step of preparing the precursor satisfies at least one of the following conditions:

[0037] (1) The mass ratio of nitrogen in the nitrogen source to phosphorus in the phosphorus source is 1:(0.5-2);

[0038] (2) The mass ratio of the pretreated biomass carbon source to the solution containing the nitrogen source and the phosphorus source is 1:10-1:1;

[0039] (3) The biomass carbon source includes at least one of bamboo, coconut shell, pistachio shell, peanut shell, straw, rice husk, and bark;

[0040] (4) The nitrogen source comprises at least one of melamine, urea, glycine, lysine and arginine;

[0041] (5) The phosphorus source includes at least one of sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium hypophosphite, ammonium phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate;

[0042] (6) In the solution containing a nitrogen source and a phosphorus source, the total concentration of the nitrogen source and the phosphorus source is 0.1 g / mL-5 g / mL;

[0043] (7) The reaction time of the pretreated biomass carbon source and the solution containing the nitrogen source and the phosphorus source is 1 h to 2 h, and the stirring rate is 50 rpm to 200 rpm.

[0044] In one embodiment, the carbonization step satisfies at least one of the following conditions:

[0045] (1) The carbonization treatment adopts a staged programmed temperature heating process, which includes: first heating to 180°C-200°C at 3°C / min-5°C / min and keeping it for 1.5h-2h, then heating to 400°C-500°C at 2°C / min-4°C / min and keeping it for 2h-3h, then heating to 700°C-800°C at a rate of 3°C / min-5°C / min and keeping it for 3h-5h, and finally heating to 1100°C-1500°C at 3°C / min-5°C / min and keeping it for 3h-5h;

[0046] (2) The carbonization treatment is carried out in a protective gas environment, wherein the protective gas includes at least one of nitrogen, argon, xenon, and radon, and the flow rate of the protective gas is 0.5L / min-1L / min.

[0047] A negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises the fast-charging negative electrode material as described above.

[0048] A battery comprises the negative electrode sheet as described above.

[0049] The preparation method described in the present invention, based on regulating the specific doping content of nitrogen and phosphorus in the precursor, utilizes the synergistic effect of two-step microwave treatment to in situ grow carbon nanotubes on the surface of nitrogen and phosphorus co-doped hard carbon, form a tight electron transport network, and optimize the electronic structure of the fast-charging negative electrode material. At the same time, controllable oxygen-containing functional group modification is achieved on the surface of the carbon nanotubes, and specific carboxyl, carbonyl, alkoxy and hydroxyl groups are introduced, thereby improving the wetting effect of the electrolyte on the fast-charging negative electrode material, promoting the embedding and extraction of ions, and improving the kinetic performance, so that the prepared fast-charging negative electrode material takes into account the conductivity, specific capacity and structural stability at the same time, and can meet the needs of high-rate fast-charging batteries, especially suitable for sodium ion fast-charging batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0051] Figure 1 This is a scanning electron microscope image of the fast-charging negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0052] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.

[0054] The invention provides a fast-charging negative electrode material, comprising nitrogen-phosphorus co-doped hard carbon and functionalized carbon nanotubes distributed on the surface of the nitrogen-phosphorus co-doped hard carbon.

[0055] In the fast-charging negative electrode material, the content of nitrogen is 0.70wt%-6.00wt%, the content of phosphorus is 1.45wt%-3.00wt%, and the functional group content on the surface of the fast-charging negative electrode material includes at least one of the following (1)-(4): in terms of oxygen atoms,

[0056] (1) 0.05wt%-0.1wt% of carboxyl groups;

[0057] (2) 0.05wt%-0.2wt% carbonyl;

[0058] (3) 0.2 wt% to 0.4 wt% of alkoxy;

[0059] (4) 0.1 wt% to 0.2 wt% of hydroxyl groups.

[0060] It should be noted that X-ray photoelectron spectroscopy is used to analyze the surface functional groups of fast-charging negative electrode materials. Based on the fact that carboxyl, carbonyl, alkoxy and hydroxyl functional groups all contain oxygen atoms and the chemical environment in which the oxygen atoms are located is different, by measuring the O1s binding energy of oxygen atoms in the material, the chemical state of oxygen atoms on the surface of the material can be revealed and the content of different functional groups can be known.

[0061] In the fast-charging negative electrode material described in the present invention, under the synergistic effect of specific contents of nitrogen and phosphorus elements and surface functionalized carbon nanotubes, not only can the electronic structure of the fast-charging negative electrode material be optimized, while the interlayer spacing is expanded, its structural stability is ensured, so that the fast-charging negative electrode material can take into account both conductivity and structural stability, but it is also beneficial to improve the wettability of the electrolyte to the fast-charging negative electrode material, promote material exchange on the negative electrode interface, enhance the kinetic performance of the fast-charging negative electrode material, and ensure the specific capacity while improving the conductivity.

[0062] Specifically, the content of nitrogen includes but is not limited to 0.70wt%, 0.80wt%, 0.90wt%, 1.00wt%, 1.10wt%, 1.15wt%, 1.20wt%, 1.25wt%, 1.30wt%, 1.35wt%, 1.40wt%, 1.45wt%, 1.50wt%, 1.55wt%, 1.60wt%, 1.70wt%, 1.75wt%, 1.80wt%, 1.85wt%, 1.90wt%, 1.95wt%, 2.00wt%, 2.05wt%, 2.10 The present invention relates to any value among wt%, 2.15wt%, 2.20wt%, 2.25wt%, 2.30wt%, 2.35wt%, 2.40wt%, 2.45wt%, 2.50wt%, 2.60wt%, 2.70wt%, 2.80wt%, 3.00wt%, 3.50wt%, 4.00wt%, 4.50wt%, 5.00wt%, 5.50wt%, 6.00wt%, or any range between any two of them, preferably 1.00wt% -4.00wt%, and more preferably 1.75wt% -2.15wt%.

[0063] The content of phosphorus element includes but is not limited to 1.45wt%, 1.50wt%, 1.55wt%, 1.60wt%, 1.65wt%, 1.70wt%, 1.75wt%, 1.80wt%, 1.85wt%, 1.90wt%, 1.95wt%, 2.00wt%, 2.05wt%, 2.10wt%, 2.15wt%, 2.20wt%, 2.25wt%, 2.30wt%, 2.35wt%, 2.40wt%, 2.45wt%, 2.50wt%, 2.60wt%, 2.70wt%, 2.80wt%, 2.90wt%, 3.00wt%, any point value or any range value between two of them, preferably 1.45wt%-2.00wt%, more preferably 1.45wt%-1.80wt%.

[0064] Preferably, the functional group content on the surface of the fast-charging negative electrode material includes, in terms of oxygen atoms, 0.05wt%-0.085wt% of carboxyl groups, and the specific content includes but is not limited to any value of 0.05wt%, 0.055wt%, 0.06wt%, 0.065wt%, 0.07wt%, 0.075wt%, 0.08wt%, 0.085wt% or any range between the two; 0.10wt%-0.20wt% of carbonyl groups, and the specific content includes but is not limited to any value of 0.10wt%, 0.11wt%, 0.12wt%, 0.15wt%, 0.16wt%, 0.18wt%, 0.20wt% or any range between the two. The range value between the two; 0.20wt%-0.35wt% alkoxy, the specific content includes but is not limited to 0.20wt%, 0.21wt%, 0.23wt%, 0.25wt%, 0.27wt%, 0.30wt%, 0.32wt%, 0.35wt% any point value or any range value between two; 0.10wt%-0.18wt% hydroxyl, the specific content includes but is not limited to 0.10wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt%, 0.15wt%, 0.16wt%, 0.17wt%, 0.18wt% any point value or any range value between two.

[0065] Preferably, the (002) crystal plane spacing of the fast-charging negative electrode material is 0.38nm-0.39nm, including but not limited to any point value among 0.3810nm, 0.3820nm, 0.3835nm, 0.3840nm, 0.3850nm, 0.3860nm, 0.3885nm or the range value between any two thereof.

[0066] Preferably, the mass of the functionalized carbon nanotubes is 0.1%-2% of the mass of the nitrogen-phosphorus co-doped hard carbon, including but not limited to any value among 0.1%, 0.2%, 0.5%, 1%, 1.2%, 1.5%, 2% or any range between two values.

[0067] Preferably, the specific surface area of ​​the fast-charging negative electrode material is 5.5 m 2 / g-6.5m 2 / g, including but not limited to 5.5m 2 / g, 5.6m 2 / g, 5.7m 2 / g, 5.8m 2 / g, 5.9m 2 / g, 6.0m 2 / g, 6.2m 2 / g, 6.5m 2 Any point value in / g or any range of values ​​between them.

[0068] Preferably, the pore volume of the fast-charging negative electrode material is 0.0175 cm 3 / g-0.0250cm 3 / g, including but not limited to 0.0175cm 3 / g, 0.0180cm 3 / g, 0.0185cm 3 / g, 0.0189cm 3 / g, 0.0205cm 3 / g, 0.0225cm 3 / g, 0.0245cm 3 Any point value in / g or any range of values ​​between them.

[0069] Preferably, D of the fast-charging negative electrode material 50 It is 5.2μm-6.5μm, including but not limited to any point value among 5.2μm, 5.3μm, 5.5μm, 5.6μm, 5.9μm, 6.2μm, 6.4μm or any range value between two of them.

[0070] Preferably, the K of the fast-charging negative electrode material 90 is 1.20-1.55, among which, K 90 =(D 90 -D 10 ) / D 50 , K 90 Including but not limited to any value among 1.25, 1.35, 1.39, 1.42, 1.46, 1.48, 1.50, 1.53, 1.55 or any range between two values.

[0071] The present invention provides a method for preparing the fast-charging negative electrode material as described above, comprising the following steps:

[0072] S1, reacting the pretreated biomass carbon source with a solution containing a nitrogen source and a phosphorus source to obtain a precursor, and carbonizing the precursor to obtain nitrogen-phosphorus co-doped hard carbon;

[0073] S2, mixing the nitrogen-phosphorus co-doped hard carbon with an iron-containing organic compound solution for impregnation reaction, and then subjecting the nitrogen-phosphorus co-doped hard carbon surface to in-situ growth of carbon nanotubes by a first microwave reaction to obtain a pre-product, wherein the power of the first microwave reaction is P1 and the time is t1;

[0074] S3, subjecting the pre-product to a second microwave reaction to obtain the fast-charging negative electrode material, wherein the power of the second microwave reaction is P2 and the time is t2.

[0075] In the nitrogen-phosphorus co-doped hard carbon obtained in step S1, the nitrogen element exists in the form of graphitized nitrogen, pyrrolic nitrogen, pyridinic nitrogen, amino group, etc., which plays a role in adjusting the electronic structure of the hard carbon and attracting reactive substances through electrostatic interaction in the subsequent impregnation reaction; the atomic radius of the phosphorus element is large, which can increase the interlayer spacing of graphite microcrystals to a certain extent, which is beneficial to further improve the kinetic properties of the hard carbon material; at the same time, POC and P=O equivalent bonds are introduced through chemical reactions to form structural distortion, which can serve as a site for sodium ion storage, which is beneficial to improve the specific capacity.

[0076] In one embodiment, by pretreating the biomass carbon source, the biomass carbon source is effectively deashed and purified, which is beneficial to improving the reversible specific capacity and initial efficiency of the finished product.

[0077] Preferably, the pretreatment comprises: reacting the biomass carbon source with the treatment solvent at 60°C-100°C at a speed of 50rpm-200rpm for 2h-8h, and then washing the reacted biomass carbon source to a neutral pH and drying it.

[0078] Further preferably, the mass ratio of the biomass carbon source to the treatment solvent is 1:10-1:1, more preferably 1:5-1:2; the treatment solvent includes at least one of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, sodium hydroxide, and potassium hydroxide, and the concentration of the treatment solvent is 0.1g / mL-5g / mL, more preferably 0.5g / mL-2g / mL.

[0079] In one embodiment, before the carbonization treatment, the pretreated biomass carbon source is first dried to reduce the moisture in the mixture, and then the carbonization treatment is performed.

[0080] Preferably, the mass ratio of nitrogen in the nitrogen source to phosphorus in the phosphorus source is 1:(0.5-2), and the specific mass ratio can be any point value among 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or a range value between any two of them.

[0081] Preferably, the mass ratio of the pretreated biomass carbon source to the solution containing the nitrogen source and the phosphorus source is 1:10-1:1, including but not limited to any point value among 1:10, 1:8, 1:6, 1:5, 1:2, 1:1 or the range value between any two of them, preferably 1:5-1:1.

[0082] Specifically, the biomass carbon source includes at least one of bamboo, coconut shell, pistachio shell, peanut shell, straw, rice husk and bark.

[0083] Specifically, the nitrogen source includes at least one of melamine, urea, glycine, lysine and arginine.

[0084] Specifically, the phosphorus source includes at least one of sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium hypophosphite, ammonium phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.

[0085] Preferably, in the solution containing a nitrogen source and a phosphorus source, the total concentration of the nitrogen source and the phosphorus source is 0.1 g / mL-5 g / mL, including but not limited to any point value among 0.1 g / mL, 0.5 g / mL, 1 g / mL, 2 g / mL, 5 g / mL or a range value between any two of them, preferably 0.1 g / mL-2 g / mL.

[0086] Preferably, the reaction time of the pretreated biomass carbon source and the solution containing the nitrogen source and the phosphorus source is 1 h-2 h, and the stirring rate is 50 rpm-200 rpm.

[0087] Preferably, the carbonization treatment adopts a staged programmed temperature rising process, which effectively improves the carbonization efficiency and carbon yield, and enriches and stabilizes the microstructure. Among them, since the biomass carbon source is rich in hemicellulose, cellulose and lignin, the three mainly lose water before 200°C; at 400°C-500°C, hydrogen, oxygen and a small amount of carbon are removed mainly in the form of H2O and CO2, which act as pore-forming agents to form a microscopic pore structure, and at the same time, carbon free radicals are formed to undergo intramolecular cyclization and aromatization rearrangement, and a carbon network plane is initially formed as a hard carbon crystalline area; at 700°C-800°C, an amorphous skeleton with lignin as a precursor is mainly formed, and then carbonization closed pores are carried out at a higher temperature, which effectively improves the carbon concentration efficiency, making the hard carbon material have better structural stability and a richer microstructure.

[0088] Specifically, the segmented programmed temperature heating process includes: first heating to 180℃-200℃ at 3℃ / min-5℃ / min and keeping warm for 1.5h-2h, then heating to 400℃-500℃ at 2℃ / min-4℃ / min and keeping warm for 2h-3h, then heating to 700℃-800℃ at a rate of 3℃ / min-5℃ / min and keeping warm for 3h-5h, and finally heating to 1100℃-1500℃ at 3℃ / min-5℃ / min and keeping warm for 3h-5h.

[0089] In one embodiment, the carbonization treatment is performed in a protective gas environment, wherein the protective gas includes at least one of nitrogen, argon, xenon, and radon, and the flow rate of the protective gas is 0.5L / min-1L / min.

[0090] In step S2 to step S3, an impregnation reaction is first performed to attract reactive substances by utilizing the electrostatic effect of the doping elements in the hard carbon, so that an organic compound containing iron is attached to the surface of the nitrogen-phosphorus co-doped hard carbon, providing a catalyst source and a carbon source for in-situ growth of carbon nanotubes, and then a first microwave reaction is performed to in-situ grow carbon nanotubes on the surface of the nitrogen-phosphorus co-doped hard carbon. This not only makes the preparation process fast, controllable, and energy-saving, but also ensures that the carbon nanotubes are tightly combined with the hard carbon, thereby forming a tight electron transmission network on the hard carbon surface. Preferably, the coating amount of carbon nanotubes on the surface of the pre-product is 0.1%-2% of the mass of the hard carbon.

[0091] After long-term testing, it was found that although the use of acidic solution and / or oxidizing solution to treat hard carbon materials with carbon nanotubes distributed on the surface can achieve the purpose of introducing oxygen-containing functional groups on its surface, this modification method has a more violent reaction. At the same time, the material itself may also change, especially the damaged carbon nanotubes may have a negative impact on the final performance of the material.

[0092] Based on this, the present invention uses a second microwave reaction in a mixture containing H, CO, CO2, CO2+ 、O2、OH、C2、CO、CO + In a highly ionized plasma environment, reasonable oxygen-containing functional group modification can be achieved on the surface of carbon nanotubes, and specific carboxyl, carbonyl, alkoxy and hydroxyl groups can be introduced, thereby improving the wetting effect of the electrolyte on the fast-charging negative electrode material, promoting the embedding and extraction of ions, and improving the kinetic performance. As a result, the prepared fast-charging negative electrode material can take into account the electrical conductivity, specific capacity and structural stability at the same time, and can meet the needs of high-rate fast-charging batteries.

[0093] Preferably, the mass ratio of the nitrogen and phosphorus co-doped hard carbon to the iron-containing organic compound solution is 1:10-1:1, including but not limited to any point value among 1:10, 1:8, 1:6, 1:5, 1:2, 1:1 or a range value between any two of them.

[0094] Specifically, the iron-containing organic compound includes at least one of heme, heme, ferrous o-phenanthroline, ferrous ethylenediaminetetraacetate, and ferrocene; in the iron-containing organic compound solution, the solvent is selected from a mixed solvent of ethanol and water, wherein the volume ratio of ethanol to water is 1:2-2:1;

[0095] Preferably, the impregnation reaction time is 0.5h-2h, and the stirring rate is 120rpm-300rpm.

[0096] Preferably, (P1-P2) / P1≥0.5, more preferably 0.5≤(P1-P2) / P1≤5. Specifically, (P1-P2) / P1 can be any value among 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.4, 3.8, 4.0, 4.2, 4.6, 4.8, 5.0 or any range between any two of them.

[0097] Preferably, (t1-t2) / t2≥5, more preferably 5≤(t1-t2) / t2≤10. Specifically, (t1-t2) / t2 can be any value among 5, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.4, 8.8, 9.0, 9.2, 9.6, 9.8, 10.0 or any range between any two of them.

[0098] Further preferably, 500W≤P1≤1500W, specifically, P1 can be any value among 500W, 550W, 600W, 650W, 700W, 750W, 800W, 850W, 900W, 950W, 1000W, 1100W, 1200W, 1300W, 1400W, 1500W, or a range value between any two of them; 20s≤t1≤100s, specifically, t1 can be any value among 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, 65s, 70s, 75s, 80s, 85s, 90s, 95s, 100s, or a range value between any two of them.

[0099] 200W≤P2≤600W. Specifically, P2 can be any value among 200W, 230W, 250W, 270W, 300W, 320W, 350W, 380W, 400W, 430W, 450W, 470W, 500W, 520W, 550W, 570W, and 600W, or a range value between any two of them; 1s≤t2≤10s, preferably 3s≤t2≤10s. Specifically, t2 can be any value among 3s, 4s, 5s, 6s, 7s, 8s, 9s, and 10s, or a range value between any two of them.

[0100] Preferably, the microwave frequencies of the first microwave reaction and the second microwave reaction are each independently selected from 2 GHz to 3 GHz.

[0101] Preferably, the second microwave reaction is carried out in a mixed gas environment of H2 and CO2, wherein the volume ratio of H2 to CO2 is 1:5-2:1, preferably 1:2-1:1.

[0102] Preferably, the pressure of the second microwave reaction is 15Pa-30Pa.

[0103] Preferably, the high voltage between the plasma generating source and the sample stage in the microwave device is 200V-1000V.

[0104] The present invention also provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer comprising the fast-charge negative electrode material as described above. It is understandable that the negative electrode active material layer may also include materials such as a binder, and the present invention does not limit this.

[0105] The present invention also provides a battery, the battery comprising the negative electrode plate as described above. It is understandable that the battery includes but is not limited to sodium ion batteries and lithium ion batteries, and is particularly suitable for sodium ion fast charging batteries. The battery also includes a positive electrode plate, a diaphragm and an electrolyte, and the present invention does not limit the positive electrode plate, the diaphragm and the electrolyte.

[0106] Hereinafter, the fast-charging negative electrode material, its preparation method and application will be further described through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0107] Example 1

[0108] Step 1: Disperse 20g of bamboo in 100mL of solution I (containing 2g / mL of HCl), place in a water bath at 80℃ and stir at 120rpm for 2h, then wash until neutral and dry. Disperse the pretreated bamboo in 100mL of solution II (containing 1g / mL of urea and 1g / mL of sodium hypophosphite), stir at 180rpm for 2h at room temperature, then evaporate the water at 80℃, place in a graphite crucible and put into a tube furnace, pass 0.5L / min of argon, and carbonize according to the following heating program: heat to 200℃ at 3.6℃ / min and keep warm for 1.5 hours, then heat to 500℃ at 3℃ / min and keep warm for 3 hours, then heat to 800℃ at 4℃ / min and keep warm for 4 hours, finally heat to 1300℃ at 5℃ / min and keep warm for 2 hours, finally cool to room temperature to obtain nitrogen-phosphorus co-doped hard carbon material.

[0109] Step 2: Take 10g of the obtained nitrogen-phosphorus co-doped hard carbon powder and disperse it in 100mL solution III (containing 1g / mL ferrocene, the solvent is 50% ethanol aqueous solution), stir and mix at 120rpm at room temperature for 1h, and then filter and separate. Ferrocene can be bound to the hard carbon surface through the π interaction between cyclopentadiene and hard carbon, providing a catalyst source and carbon source for in-situ growth of carbon nanotubes. Then place it in a microwave reaction chamber for microwave reaction, the reaction conditions are: frequency 2.5GHz, power 800W, lasting 30s, to obtain a pre-product.

[0110] Step 3: Take 10g of the obtained pre-product and spread it in a glass dish, place it in a microwave plasma reaction chamber, evacuate it, and introduce a mixture of H2 and CO2 with a volume ratio of 1:1, and keep the pressure in the chamber at about 20Pa. Set the voltage between the microwave plasma source and the sample stage to 500V, the microwave frequency to 2GHz, the power to 300W, and the reaction time to 4s. After the reaction, a fast-charge negative electrode material is obtained.

[0111] The fast-charge negative electrode material prepared in Example 1 was characterized and tested, and the results were as follows: Figure 1 As shown, it can be seen that the surface of the fast-charging negative electrode material is coated with a carbon nanotube network structure.

[0112] Example 2

[0113] The difference between Example 2 and Example 1 is that in step 1, 20 g of peanut shells are dispersed in 100 mL of solution I (containing 2 g / mL HCl), placed in an 80° C. water bath and stirred at 120 rpm for 2 h, then washed to neutrality and dried. The pretreated peanut shells were dispersed in 100 mL of solution II (containing 0.6 g / mL melamine and 1.2 g / mL ammonium dihydrogen phosphate), stirred at 180 rpm for 2 h at room temperature, then evaporated at 80 °C, placed in a graphite crucible and put into a tubular furnace, introduced with 0.5 L / min argon, and carbonized according to the following heating program: heat to 200 °C at 3.6 °C / min and keep warm for 2 hours, then heat to 500 °C at 3 °C / min and keep warm for 3 hours, then heat to 800 °C at 4 °C / min and keep warm for 4 hours, finally heat to 1300 °C at 5 °C / min and keep warm for 2 hours, and finally cool to room temperature to obtain nitrogen-phosphorus co-doped hard carbon material.

[0114] Example 3

[0115] The difference between Example 3 and Example 1 is that the bark of the same mass is used instead of bamboo. In step 2, 10g of the obtained nitrogen-phosphorus co-doped hard carbon powder is dispersed in 100mL solution III (containing 1g / mL o-phenanthroline ferrous acid, the solvent is 50% ethanol aqueous solution), stirred and mixed at 120rpm at room temperature for 1h, and then filtered and separated. The o-phenanthroline ferrous acid can be bound to the hard carbon surface through the π interaction between o-phenanthroline and hard carbon, providing a catalyst source and carbon source for in-situ growth of carbon nanotubes. Then placed in a microwave reaction chamber for microwave reaction, the reaction conditions: frequency 2GHz, power 1000W, lasting 25s, to obtain a pre-product.

[0116] Example 4

[0117] The difference between Example 4 and Example 1 is that coconut shell of equal mass is used instead of bamboo. In step 3, 10g of the obtained pre-product is spread in a glass dish, placed in a microwave plasma reaction chamber, evacuated, and a mixture of H2 and CO2 with a volume ratio of 2:3 is introduced to maintain the pressure in the chamber at about 25Pa. The voltage between the microwave plasma source and the sample stage is set to 800V, the microwave frequency is 2.5GHz, the power is 400W, and the reaction time is 3s. After the reaction is completed, a fast-charged negative electrode material is obtained.

[0118] Example 5

[0119] Step 1: Disperse 20g of bamboo in 100mL of solution I (containing 1g / mL of sodium hydroxide), place in a 90℃ water bath and stir at 140rpm for 5h, then wash until neutral and dry. Disperse the pretreated bamboo in 100mL of solution II (containing 1.5g / mL of urea and 1g / mL of sodium hypophosphite), stir at 150rpm for 1.5h at room temperature, then evaporate the water at 80℃, place in a graphite crucible and put into a tube furnace, pass 1L / min of nitrogen, and carbonize according to the following heating program: heat to 190℃ at 4.2℃ / min and keep warm for 1.8 hours, then heat to 420℃ at 2.8℃ / min and keep warm for 2.5 hours, then heat to 780℃ at 3.5℃ / min and keep warm for 4.4h, finally heat to 1350℃ at 5℃ / min and keep warm for 4.5 hours, finally cool to room temperature to obtain nitrogen-phosphorus co-doped hard carbon material.

[0120] Step 2: Take 10g of the obtained nitrogen-phosphorus co-doped hard carbon powder and disperse it in 100mL solution III (containing 0.5g / mL ferrocene, the solvent is 50% ethanol aqueous solution), stir and mix at 200rpm at room temperature for 0.8h, and then filter and separate. Ferrocene can be bound to the hard carbon surface through the π interaction between cyclopentadiene and hard carbon, providing a catalyst source and carbon source for in-situ growth of carbon nanotubes. Then place it in a microwave reaction chamber for microwave reaction, the reaction conditions are: frequency 2.5GHz, power 1000W, lasting 25s, to obtain a pre-product.

[0121] Step 3: Take 10g of the obtained pre-product and spread it in a glass dish, place it in a microwave plasma reaction chamber, evacuate it, and introduce a mixture of H2 and CO2 with a volume ratio of 1:1, and keep the pressure in the chamber at about 20Pa. Set the voltage between the microwave plasma source and the sample stage to 500V, the microwave frequency to 2GHz, the power to 400W, and the reaction time to 5s. After the reaction, a fast-charge negative electrode material is obtained.

[0122] Comparative Example 1

[0123] Step 1: Disperse 20g of pistachio shell in 100mL of solution I (containing 2g / mL of NaOH), place in a water bath at 80℃ and stir at 120rpm for 2h. Then wash until neutral and dry. Then place in a graphite crucible and put into a tube furnace, pass 0.5L / min of argon, and carbonize according to the following heating program: heat to 200℃ at 3.6℃ / min and keep warm for 1.5 hours, then heat to 500℃ at 3℃ / min and keep warm for 3 hours, then heat to 800℃ at 4℃ / min and keep warm for 4 hours, finally heat to 1300℃ at 5℃ / min and keep warm for 2 hours, finally cool to room temperature to obtain hard carbon material.

[0124] Step 2: Take 10g of the obtained hard carbon powder and disperse it in 100mL solution III (containing 1g / mL ferrocene, the solvent is 50% ethanol aqueous solution), stir and mix at 120rpm at room temperature for 1h, and then filter and separate. Ferrocene can be bound to the hard carbon surface through the π interaction between cyclopentadiene and hard carbon, providing a catalyst source and carbon source for in-situ growth of carbon nanotubes. Then place it in a microwave reaction chamber for microwave reaction, the reaction conditions are: frequency 2.5GHz, power 800W, lasting 30s, to obtain carbon nanotube-coated hard carbon.

[0125] Step 3: Take 10g of the obtained carbon nanotube-coated hard carbon and spread it in a glass dish, place it in a microwave plasma reaction chamber, evacuate it, and introduce a mixture of H2 and CO2 with a volume ratio of 1:1, and keep the pressure in the chamber at about 20 Pa. Set the voltage between the microwave plasma source and the sample stage to 500V, the microwave frequency to 2GHz, the power to 300W, and the reaction time to 4s. After the reaction, the negative electrode material is obtained.

[0126] Comparative Example 2

[0127] Step 1: Disperse 20g peanut shells in 100mL solution Ⅰ (containing 2g / mL HCl), place in a 80℃ water bath and stir at 120rpm for 2h. Then wash until neutral and dry. Disperse the pretreated peanut shells in 100mL solution Ⅱ (containing 0.6g / mL melamine and 1.2g / mL diammonium phosphate), stir at 180rpm for 2h at room temperature, and then evaporate the water at 80℃. Place the obtained precursor in a graphite crucible and put it into a tube furnace, pass 0.5L / min nitrogen, and carbonize according to the following heating program: heat to 200℃ at 3.6℃ / min and keep warm for 2 hours, then heat to 500℃ at 3℃ / min and keep warm for 3 hours, then heat to 800℃ at 4℃ / min and keep warm for 4 hours, finally heat to 1300℃ at 5℃ / min and keep warm for 2 hours, and finally cool to room temperature to obtain nitrogen-phosphorus co-doped hard carbon material.

[0128] Step 2: Take 10g of the obtained nitrogen-phosphorus-doped hard carbon and spread it in a glass dish, place it in a microwave plasma reaction chamber, evacuate it, and introduce a mixture of H2 and CO2 with a volume ratio of 1:1, and keep the pressure in the chamber at about 20 Pa. Set the voltage between the microwave plasma source and the sample stage to 500V, the microwave frequency to 2GHz, the power to 300W, and the reaction time to 4s. After the reaction, the negative electrode material is obtained.

[0129] Comparative Example 3

[0130] Step 1: Disperse 20g coconut shell in 100mL solution Ⅰ (containing 2g / mL HCl), place in a 80℃ water bath and stir at 120rpm for 2h. Then wash to neutrality and dry. Disperse the pretreated coconut shell in 100mL solution Ⅱ (containing 1g / mL urea and 1g / mL sodium hypophosphite), stir at 180rpm for 2h at room temperature, and then evaporate the water at 80℃. The obtained precursor is placed in a graphite crucible and placed in a tube furnace, and 0.5L / min argon is introduced. Carbonization is carried out according to the following heating program: heat to 200℃ at 3.6℃ / min and keep warm for 1.5 hours, then heat to 500℃ at 3℃ / min and keep warm for 3 hours, then heat to 800℃ at 4℃ / min and keep warm for 4 hours, finally heat to 1300℃ at 5℃ / min and keep warm for 2 hours, and finally cool to room temperature to obtain nitrogen-phosphorus co-doped hard carbon material.

[0131] Step 2: Take 10g of the obtained nitrogen and phosphorus co-doped hard carbon powder and 0.02g of carbon nanotubes and disperse them in 50mL of ethanol (75%), stir and mix at 120rpm at room temperature for 1h, evaporate the solvent, and obtain carbon nanotube-coated nitrogen and phosphorus doped hard carbon.

[0132] Step 3: Take 10g of the obtained carbon nanotube-coated nitrogen-phosphorus-doped hard carbon and spread it in a glass dish, place it in a microwave plasma reaction chamber, evacuate it, and introduce a mixture of H2 and CO2 with a volume ratio of 2:3, and keep the pressure in the chamber at about 25 Pa. Set the voltage between the microwave plasma source and the sample stage to 800V, the microwave frequency to 2.5GHz, the power to 400W, and the reaction time to 3s. After the reaction, the negative electrode material is obtained.

[0133] Comparative Example 4

[0134] The difference between Comparative Example 4 and Example 3 is that step 3 is not performed, and the nitrogen and phosphorus doped hard carbon coated with carbon nanotubes prepared in step 2 is used as the negative electrode material.

[0135] Comparative Example 5

[0136] The difference between Comparative Example 5 and Example 1 is that the microwave reaction time in step 3 is 20 s.

[0137] Comparative Example 6

[0138] The difference between Comparative Example 6 and Example 1 is that in step 2, the microwave power is 600 W and the time is 25 s; in step S3, the microwave power is 400 W and the time is 10 s.

[0139] Comparative Example 7

[0140] The difference between Comparative Example 7 and Example 1 is that the microwave time in step 2 is 25 s; and the microwave time in step S3 is 10 s.

[0141] Comparative Example 8

[0142] The difference between Comparative Example 8 and Example 1 is that the microwave power in step 2 is 600 W; and the microwave power in step S3 is 400 W.

[0143] The negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-8 were characterized and tested, and the test results are shown in Table 1. The specific surface area and total pore volume of the negative electrode materials were measured using nitrogen adsorption and desorption methods; the particle size and distribution width of the negative electrode materials were measured using a laser particle size analyzer; the (002) crystal plane spacing of the negative electrode materials was calculated using the Bragg formula using an X-ray diffractometer; and the N and P contents in the negative electrode materials were measured using an organic element analyzer.

[0144] Table 1

[0145]

[0146] The surface functional groups of the negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-8 were analyzed by X-ray photoelectron spectroscopy. The results are shown in Table 2 (based on oxygen atoms).

[0147] Table 2

[0148]

[0149]

[0150] The negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-8 were assembled into batteries.

[0151] The specific steps are as follows: the obtained negative electrode material, conductive agent Super P, dispersant CMC, and binder PVDF are mixed in a mass ratio of 70:15:5:10 to prepare a slurry; the negative electrode slurry is coated on aluminum foil with a 75μm scraper, dried in a blast drying oven for 4 hours, and dried in a vacuum drying oven for 12 hours. After rolling and cutting, a hard carbon electrode pole piece is obtained. After the pole piece is placed in a vacuum drying oven and dried for 1 hour, it is transferred to an argon atmosphere glove box and assembled into a C2032 button battery in the order of "negative electrode shell → pole piece → diaphragm → electrolyte → glass fiber → electrolyte → sodium sheet → gasket → shrapnel → positive electrode shell". Among them, the electrolyte contains 1 mol / L sodium salt (NaPF6), ethylene carbonate solvent (EC, 99.9%), diethyl carbonate (DEC, 99.9%), and ethylene glycol dimethyl ether (DME, 99.9%).

[0152] The prepared button battery was subjected to charge and discharge cycles, and the charge and discharge conditions were as follows:

[0153] Use the Blue Power Battery Test System to test the charge and discharge of button batteries. The voltage test range is 0.005~2V (vs.Na / Na + ), discharge at 0.1C to 0.005V; charge at 0.1C to 2V, and test the reversible capacity and first coulombic efficiency of the button battery.

[0154] Rate performance test: Voltage test range 0.005~2V(vs.Na / Na + ), discharged to 0.005V at 1C, 2C, and 3C respectively, and then charged to 2V at the same rate, and the reversible capacity retention rate of the button battery at different rates relative to 0.1C was detected, where capacity retention rate = (reversible specific capacity at 1C / 2C / 3C) / reversible specific capacity at 0.1C × 100%.

[0155] When assembling the battery, five batteries were prepared for each test, and a total of five sets of data were tested. The final performance was the average of the five sets of data. The reversible capacity, first coulombic efficiency and cycle performance data are shown in Table 3; the rate performance data are shown in Table 4.

[0156] Table 3

[0157]

[0158] According to Table 3, Examples 1-5 have higher reversible specific capacity and first coulombic efficiency than Comparative Examples 1-8. The reason may be that, on the one hand, thanks to the co-doping of N and P, active sites such as pyridine N, POC, and P=O are introduced into the hard carbon as sodium storage active sites; on the other hand, the in-situ grown carbon nanotubes effectively improve the conductivity of the hard carbon, and the functionalization significantly improves the wettability of the electrolyte to the negative electrode particles. The surface of Comparative Example 5 consumes a large amount of Na due to the introduction of excessive oxygen-containing functional groups. + , forming irreversible capacity, so the reversible specific capacity and first efficiency are lower. Comparative Example 6-7 Due to the long microwave treatment time in step 3, too many functional groups were generated, consuming a large amount of Na + , forming irreversible capacity, so the reversible specific capacity and first efficiency are lower.

[0159] Table 4

[0160]

[0161]

[0162] According to Table 4, Examples 1-5 have higher capacity retention and better rate performance than Comparative Examples 1-8. The reason may be that, firstly, thanks to the co-doping of N and P, the electronic structure of the negative electrode material is effectively optimized and the interlayer spacing is enlarged; secondly, the in-situ grown carbon nanotubes effectively improve the conductivity of hard carbon and promote electron transfer; thirdly, the functionalization of carbon tubes significantly improves the wettability of the electrolyte to the negative electrode particles and promotes the material exchange on the negative electrode interface. The three synergistically enhance the kinetic performance of the obtained negative electrode material.

[0163] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0164] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A fast-charging negative electrode material, characterized in that: The fast-charging negative electrode material includes nitrogen-phosphorus co-doped hard carbon and functionalized carbon nanotubes distributed on the surface of the nitrogen-phosphorus co-doped hard carbon; In the fast-charging negative electrode material, the content of nitrogen is 0.70wt%-6.00wt%, the content of phosphorus is 1.45wt%-3.00wt%, and the functional group content on the surface of the fast-charging negative electrode material includes at least one of the following (1)-(4): in terms of oxygen atoms, (1) 0.05wt%-0.1wt% of carboxyl groups; (2) 0.05wt%-0.2wt% carbonyl; (3) 0.2 wt% to 0.4 wt% of alkoxy; (4) 0.1 wt% to 0.2 wt% of hydroxyl groups.

2. The fast-charging negative electrode material according to claim 1, characterized in that: The fast-charge negative electrode material meets at least one of the following conditions: (1) The (002) interplanar spacing of the fast-charging negative electrode material is 0.38 nm to 0.39 nm; (2) The mass of the functionalized carbon nanotubes is 0.1%-2% of the mass of the nitrogen-phosphorus co-doped hard carbon; (3) The specific surface area of ​​the fast-charging negative electrode material is 5.5 m 2 / g-6.5m 2 / g; (4) The pore volume of the fast-charging negative electrode material is 0.0175 cm 3 / g-0.0250cm 3 / g; (5) D of the fast-charging negative electrode material 50 5.2μm-6.5μm; (6) K of the fast-charging negative electrode material 90 is 1.20-1.55, among which, K 90 =(D 90 -D 10 ) / D 50 .

3. A method for preparing a fast-charging negative electrode material as claimed in claim 1 or 2, characterized in that: The steps include: The pretreated biomass carbon source is reacted with a solution containing a nitrogen source and a phosphorus source to obtain a precursor, and the precursor is subjected to carbonization treatment to obtain nitrogen-phosphorus co-doped hard carbon; After the nitrogen-phosphorus co-doped hard carbon is mixed with an iron-containing organic compound solution for impregnation reaction, carbon nanotubes are grown in situ on the surface of the nitrogen-phosphorus co-doped hard carbon through a first microwave reaction to obtain a pre-product, wherein the power of the first microwave reaction is P1 and the time is t1; The pre-product is subjected to a second microwave reaction to obtain the fast-charging negative electrode material, wherein the power of the second microwave reaction is P2 and the time is t2.

4. The method for preparing the fast-charging negative electrode material according to claim 3, characterized in that: 500W≤P1≤1500W, 20s≤t1≤100s; and / or, 200W≤P2≤600W, 1s≤t2≤10s; And / or, (P1-P2) / P1≥0.5, (t1-t2) / t2≥5.

5. The method for preparing the fast-charging negative electrode material according to claim 3 or 4, characterized in that: The first microwave reaction and the second microwave reaction also satisfy at least one of the following conditions: (1) The microwave frequencies of the first microwave reaction and the second microwave reaction are each independently selected from 2 GHz to 3 GHz; (2) the second microwave reaction is carried out in a mixed gas environment of H2 and CO2, wherein the volume ratio of H2 to CO2 is 1:5-2:1; (3) The pressure of the second microwave reaction is 15Pa-30Pa.

6. The method for preparing a fast-charging negative electrode material according to claim 3, characterized in that: The impregnation reaction step satisfies at least one of the following conditions: (1) The mass ratio of the nitrogen and phosphorus co-doped hard carbon to the iron-containing organic compound solution is 1:10-1:1; (2) the iron-containing organic compound comprises at least one of heme, heme, ferrous ferrocyanide, ferrous ethylenediaminetetraacetate, and ferrocene; (3) In the iron-containing organic compound solution, the solvent is selected from a mixed solvent of ethanol and water, wherein the volume ratio of ethanol to water is 1:2-2:1; (4) The impregnation reaction time is 0.5h-2h, and the stirring rate is 120rpm-300rpm.

7. The method for preparing a fast-charging negative electrode material according to claim 3, characterized in that: The pretreatment comprises: stirring the biomass carbon source and the treatment solvent at 60°C-100°C at a speed of 50rpm-200rpm for 2h-8h, and then washing the reacted biomass carbon source until the pH is neutral and drying it.

8. The method for preparing a fast-charging negative electrode material according to claim 3, characterized in that: The step of preparing the precursor satisfies at least one of the following conditions: (1) The mass ratio of nitrogen in the nitrogen source to phosphorus in the phosphorus source is 1:(0.5-2); (2) The mass ratio of the pretreated biomass carbon source to the solution containing the nitrogen source and the phosphorus source is 1:10-1:1; (3) The biomass carbon source includes at least one of bamboo, coconut shell, pistachio shell, peanut shell, straw, rice husk, and bark; (4) The nitrogen source comprises at least one of melamine, urea, glycine, lysine and arginine; (5) The phosphorus source includes at least one of sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium hypophosphite, ammonium phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; (6) In the solution containing a nitrogen source and a phosphorus source, the total concentration of the nitrogen source and the phosphorus source is 0.1 g / mL-5 g / mL; (7) The reaction time of the pretreated biomass carbon source and the solution containing the nitrogen source and the phosphorus source is 1 h to 2 h, and the stirring rate is 50 rpm to 200 rpm.

9. The method for preparing a fast-charging negative electrode material according to claim 3, characterized in that: The carbonization step satisfies at least one of the following conditions: (1) The carbonization treatment adopts a staged programmed temperature heating process, which includes: first heating to 180°C-200°C at 3°C / min-5°C / min and keeping it for 1.5h-2h, then heating to 400°C-500°C at 2°C / min-4°C / min and keeping it for 2h-3h, then heating to 700°C-800°C at a rate of 3°C / min-5°C / min and keeping it for 3h-5h, and finally heating to 1100°C-1500°C at 3°C / min-5°C / min and keeping it for 3h-5h; (2) The carbonization treatment is carried out in a protective gas environment, wherein the protective gas includes at least one of nitrogen, argon, xenon, and radon, and the flow rate of the protective gas is 0.5L / min-1L / min.

10. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the fast-charging negative electrode material as claimed in claim 1 or 2.

11. A battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 10.